Mapping the link between graduating nursing students’ professional competence and educational components : a scoping review - Kielė, Viktorija; Koskinen, Sanna; Istomina, Natalja; Truš, Marija; Leino-Kilpi, Helena (University of Ostrava, 2025)
Aim: To explore the link between nurse professional competence and various educational components within nursing education based on empirical evidence.
Design: A scoping review.
Methods: A comprehensive literature search was conducted from 1999 to 2024 using the Academic Search Premier, Business Source Complete, CINAHL, Education Research Complete, ERIC, and PubMed databases. Data were analysed using thematic analysis.
Results: Thirty relevant studies met the inclusion criteria. The identified competencies were grouped into three main categories: management, nursing intervention, and societal and social competencies. Educational components were divided into two main categories: directive-regulated curricula and optional educational components. Most nurse competencies were linked to one or more educational components.
Conclusion:  This review found that competencies such as patient care initiation, interprofessional teamwork and nurse leadership received more research attention than others. The most frequently studied educational components were study modules / training in nursing curricula and clinical placements. However, no clear link was found between nurse competence and educational components for graduate nurses.